Analysis of Problem-Solving Ability in Mathematics Learning for Grade VI Elementary School Students - E Silmi Kaaffahi; Yunus Abidin; Tita Mulyati (Journal of Future Education, 2025)
This study aimed to analyze elementary students’ mathematical problem-solving skills through a contextual geometry assessment focused on rectangular shapes. The research involved 36 sixth-grade students who completed five open-ended problem-solving tasks designed to measure four aspects of problem-solving: modeling the problem, identifying relevant information or constraints, reasoning with data, and drawing conclusions. Student responses were evaluated using an analytic rubric with a maximum total score of 15. The results showed that the average student achievement was 76.67%, indicating a moderate to good level of problem-solving ability. Students demonstrated strong performance in understanding and modeling the problem context, with the highest mean score obtained in this aspect. However, reasoning with data emerged as the weakest area, as many students experienced difficulties in explaining solution procedures clearly and systematically, despite obtaining correct final answers. Students’ ability to draw conclusions based on mathematical evidence was adequate but not yet consistent. In conclusion, the findings suggest that while contextual problems support students’ initial understanding, greater instructional emphasis is needed on reasoning processes, procedural explanation, and evidence-based conclusions to strengthen overall mathematical problem-solving skills at the elementary level.